Pengelolaan Air Asam Tambang dari Batuan Sisa di Pit Barani dan Ramba Joring serta Aplikasi Model Enkapsulasi pada Bendungan Tailing di Tambang Emas Martabe - Latipa Henim Siregar; Zulkifli Nasution; Fatimah Fatimah (Jurnal Serambi Engineering, 2021)
Acid mine drainage is one of the significant negative impacts of  mining activities that can result  in environmental degradation. Waste rock is  mine waste that is found in large quantities and can produce acid mine drainage (AMD). This study aims to identify  waste rock which has  the potential to generate acidity (PAF) and do not generate acidity (NAF) in the Barani and Ramba Joring pits and the application of the encapsulation model in  tailings dams. The research method with the encapsulation model is a simple method designed in tailings dams to encapsulate the PAF with the NAF. Rock characterization and geochemical analysis will result in the rock being classified  as  PAF and NAF in both wells . The data used for this study are drilling data (cutting) data that include rock lithology and chemical quality (NAPP and NAG) data. The results identified that the PAF was dominant relative to the  NAF  both wells  and the waste rock in the Barani pit was at a  higher risk of producing acidity than the Ramba Joring pit. Measurements of oxygen diffusion and surface water quality indicated that encapsulation of waste rock in the tailings dam may  prevent the formation of acidic mine drainage